Tagging and catching: rapid isolation and efficient labeling of organelles using the covalent Spy-System in planta - Martina Lang; Marlene Pröschel; Nico Brüggen; Uwe Sonnewald (Plant Methods, 2020)
Abstract Background Up-to-now, several biochemical methods have been developed to allow specific organelle isolation from plant tissues. These procedures are often time consuming, require substantial amounts of plant material, have low yield or do not result in pure organelle fractions. Moreover, barely a protocol allows rapid and flexible isolation of different subcellular compartments. The recently published SpySystem enables the in vitro and in vivo covalent linkage between proteins and protein complexes. Here we describe the use of this system to tag and purify plant organelles. Results We developed a simple and specific method to in vivo tag and visualize, as well as isolate organelles of interest from crude plant extracts. This was achieved by expressing the covalent split-isopeptide interaction system, consisting of SpyTag and SpyCatcher, in Nicotiana benthamiana leaves. The functionality of the SpySystem in planta, combined with downstream applications, was proven. Using organelle-specific membrane anchor sequences to program the sub-cellular localization of the SpyTag peptide, we could tag the outer envelope of chloroplasts and mitochondria. By co-expression of a cytosolic, soluble eGFP-SpyCatcher fusion protein, we could demonstrate intermolecular isopeptide formation in planta and proper organelle targeting of the SpyTag peptides to the respective organelles. For one-step organelle purification, recombinantly expressed SpyCatcher protein was immobilized on magnetic microbeads via covalent thiol-etherification. To isolate tagged organelles, crude plant filtrates were mixed with SpyCatcher-coated beads which allowed isolation of SpyTag-labelled chloroplasts and mitochondria. The isolated organelles were intact, showed high yield and hardly contaminants and can be subsequently used for further molecular or biochemical analysis. Conclusion The SpySystem can be used to in planta label subcellular structures, which enables the one-step purification of organelles from crude plant extracts. The beauty of the system is that it works as a covalent toolbox. Labeling of different organelles with individual tags under control of cell-specific and/or inducible promoter sequences will allow the rapid organelle and cell-type specific purification. Simultaneous labeling of different organelles with specific Tag/Catcher combinations will enable simultaneous isolation of different organelles from one plant extract in future experiments.